2022
DOI: 10.1038/s41598-022-23980-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibiotic-resistance traits in Akkermansia muciniphila strains of human origin

Abstract: Akkermansia muciniphila, a commensal bacterium commonly found in healthy gut microbiota, is widely considered a next-generation beneficial bacterium candidate to improve metabolic and inflammatory disorders. Recently the EFSA’s Panel on Nutrition, Novel food, and Food Allergens has declared that pasteurized A. muciniphila DSM 22959T (also MucT, ATCC BAA-835) can be considered safe as a novel food, opening the door to its commercialization as a food supplement. Despite its recognized health benefits, there is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Specifically, a total of 538 and 204 hits were generated among B. fragilis sensu stricto (n=275) and B. fragilis A (n=102) genomes, respectively, for the presence of adeF that confers resistance to fluoroquinolone and tetracycline antibiotics by acting as an efflux pump component [74]. This AMR gene has been detected previously among Bacteroides clinical isolates as well as being prevalent among other gut-associated bacteria including Akkermansia muciniphila and the pathogen Acinetobacter baumannii [75][76][77][78]. Tetracycline resistance gene variants were also detected among B. fragilis sensu stricto and B. fragilis A genomes, including tetB, tetC, tetM, tetQ and tetX.…”
Section: Amr Genes Encoded In B Fragilis Genomesmentioning
confidence: 99%
“…Specifically, a total of 538 and 204 hits were generated among B. fragilis sensu stricto (n=275) and B. fragilis A (n=102) genomes, respectively, for the presence of adeF that confers resistance to fluoroquinolone and tetracycline antibiotics by acting as an efflux pump component [74]. This AMR gene has been detected previously among Bacteroides clinical isolates as well as being prevalent among other gut-associated bacteria including Akkermansia muciniphila and the pathogen Acinetobacter baumannii [75][76][77][78]. Tetracycline resistance gene variants were also detected among B. fragilis sensu stricto and B. fragilis A genomes, including tetB, tetC, tetM, tetQ and tetX.…”
Section: Amr Genes Encoded In B Fragilis Genomesmentioning
confidence: 99%
“…Based on the antibiotic susceptibility evaluation tests, it was found that AKK PROBIO was indeed resistant to moxifloxacin. All A. muciniphila strains, including the type strain, showed low sensitivity to ciprofloxacin [44]. Both moxifloxacin and ciprofloxacin are quinolone antibiotics, so A. muciniphila may be innately resistant to quinolone antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction yielded only three resistance genes belonging to two categories, indicating that AKK PROBIO is susceptible to the majority of antibiotics. According to the study by Filardi et al, all strains of A. muciniphila harbor the gene adeF, encoding for a subunit of the resistance-nodulation-cell division efflux pump system [44].…”
Section: Discussionmentioning
confidence: 99%
“…The total cell count and viability of the bacterial cultures were assessed by flow cytometry, following the ISO 10932 procedure [ 40 ], with some modifications as previously reported [ 41 ]. Bacterial cultures were grown at 30 °C for 24 h in ISO-Sensitest broth (Oxoid) supplemented with 10% v / v MRS (Oxoid) and diluted in filtered phosphate-buffered saline (PBS, pH = 7.4) to achieve a concentration of approximately 1.0 × 10 6 cells/mL.…”
Section: Methodsmentioning
confidence: 99%